Non-linear relationship of serum albumin-to-globulin ratio and cognitive function in American older people: a cross-sectional national health and nutrition examination survey 2011–2014 (NHANES) study - Yang, Hang; Liao, Zhenyi; Zhou, Ye; Gao, Zhenzhen; Mao, Yajun (Frontiers in Public Health, 2024)
Background: Inflammation and liver function are associated with cognitive decline and dementia.Little is known about the serum albumin-to-globulin ratio on cognitive function.The objective of this study was to investigate the association between albumin-toglobulin ratio and cognitive function among the American older people. Methods: The public data available on the US National Health and Nutrition Examination Survey (NHANES) from 2011 to 2014 was used for this cross-sectional study. Participants aged ³ 60 years completed the cognitive function assessments, including word learning and recall modules from the Consortium to Establish a Registry for Alzheimer's Disease (CERAD), the animal fluency (AF)test, and the digit symbol substitution test (DSST). A composite cognition score was calculated to evaluate global cognition. The univariate and multivariate linear regression analysis, curve fitting, a threshold effect, along with a subgroup analysis and interaction tests were conducted.Results: Serum albumin-to-globulin ratio (per 0.1 unit) was positively associated DSST score (β = 0.36, 95% CI: 0.21, 0.51), AF score (β = 0.1, 95% CI: 0.04, 0.16) and global cognition score (β = 0.05, 95% CI: 0.02, 0.07), after being fully adjusted, while albumin-to-globulin ratio was not related to CERAD score (β = 0.05, 95% CI: -0.02, 0.12). A non-linear was observed in the dose-response relationship between albumin-to-globulin ratio and global cognition (P for non-linearity < 0.001).The subgroup analysis was overall stable, yet the interaction test was significant for age on global cognition (P for interaction = 0.036).The findings of this cross-sectional study suggested a positive and non-linear association between albumin-to-globulin ratio and cognitive function in the American older people.Maintaining albumin-to-globulin ratio with an appropriate range may be one of the therapeutic strategies to limit the progression of cognitive decline for the older people.